Carving Superior Character Through 5S Culture: The Role of Teachers in Madrasah Ibtidaiyah - Sekar Ayu Safira; Iqnatia Alfiansyah (Postgraduate, University of Mataram, 2023)
This research aims to explore the routines carried out by children to shape student character by the provisions of Minister of Education and Culture Regulation No. 20 of 2018 concerning Character Strengthening. A qualitative approach with a phenomenological type was used in this research to gain an in-depth understanding of this phenomenon. The results of this research identified seven strategies used in implementing character education based on Minister of Education and Culture Regulation No. 20 of 2018. In addition, and this research highlights efforts to foster positive interactions between students, protect themselves and the school environment through routines, facilitate the development of students' maximum potential, and invite participation from parents and the school community through routines. This research contributes to understanding how the implementation of character education in elementary schools can be successful objectives set out in Minister of Education and Culture Regulation no. 20 of 2018. By implementing these strategies, strengthening student character can be achieved effectively by relevant policies, management, and learning curriculum. The results of this research open the door to a better understanding of character education efforts at the elementary level and may provide insight for improving this process in the future.